2016
DOI: 10.1186/s13059-016-1078-x
|View full text |Cite
|
Sign up to set email alerts
|

Capture Hi-C identifies a novel causal gene, IL20RA, in the pan-autoimmune genetic susceptibility region 6q23

Abstract: BackgroundThe identification of causal genes from genome-wide association studies (GWAS) is the next important step for the translation of genetic findings into biologically meaningful mechanisms of disease and potential therapeutic targets. Using novel chromatin interaction detection techniques and allele specific assays in T and B cell lines, we provide compelling evidence that redefines causal genes at the 6q23 locus, one of the most important loci that confers autoimmunity risk.ResultsAlthough the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 101 publications
1
80
0
1
Order By: Relevance
“…Genome-wide association studies (GWAS) in the last decade have associated 324 distinct genomic regions to at least one and often several autoimmune diseases ( http://www.immunobase.org ). The majority of associated variants lie outside genes [1] and presumably tag regulatory variants acting on nearby or more distant genes [2,3] . Progress from GWAS discovery to biological interpretation has been hampered by lack of systematic methods to define the gene(s) regulated by a given variant.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) in the last decade have associated 324 distinct genomic regions to at least one and often several autoimmune diseases ( http://www.immunobase.org ). The majority of associated variants lie outside genes [1] and presumably tag regulatory variants acting on nearby or more distant genes [2,3] . Progress from GWAS discovery to biological interpretation has been hampered by lack of systematic methods to define the gene(s) regulated by a given variant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using Hi-C, a recent study demonstrated that the non-coding region on chromosome 6 containing a variant that has been associated with RA and psoriasis, interacts not only with the promoter of TNFAIP3, the closest gene, but also with IL20RA. 48 Furthermore, a comprehensive examination of 17 human primary blood cell types found an enrichment of autoimmune disease SNPs in Hi-C domains in lymphoid cells compared with myeloid cells. 49 The authors identified that the majority of identified genes (76%) had not been previously linked with immune-mediated diseases.…”
Section: Co-localization Of Snps With Chromatin Marks Points To Diseamentioning
confidence: 99%
“…Recently, there has been a growing interest in using chromatin conformation and other functional genomics techniques to describe these disease-associated loci and identify the genes that are affected by them. Previous studies have used techniques such as Capture Hi-C and HiChIP to link the genes that physically interact with disease associated loci (Dryden et al 2014;Jäger et al 2015;Martin et al 2015Martin et al , 2016Cairns et al 2016;McGovern et al 2016;Mumbach et al 2017).…”
Section: Introductionmentioning
confidence: 99%